Soccer injuries and recovery in dutch male amateur soccer players: Results of a prospective cohort study - van Beijsterveldt, A. M.; Steffen, K.; Stubbe, J. H.; Frederiks, J. E.; van de Port, I. G. L.; Backx, F. J. G. (Clinical Journal of Sport Medicine, 2014)
Objective: To describe characteristics of outdoor soccer injury and recovery among Dutch soccer players.